1999
DOI: 10.1007/s004240051092
|View full text |Cite
|
Sign up to set email alerts
|

Brain, abdominal and arterial blood temperatures of free-ranging eland in their natural habitat

Abstract: Using implanted miniature data loggers we measured brain, arterial blood and abdominal temperatures at 5-min intervals in two free-ranging eland (Tragelaphus oryx) in their natural habitat. The animals were subjected to a nychthemeral range of globe temperature which exceeded 40 degrees C. Arterial blood exhibited a moderate amplitude (2.3 degrees C) nychthemeral rhythm, with a temperature peak at 1600-1800 hours, and a trough in the early morning at 0600-0800 hours. Mean abdominal temperature was 0.2-0.3 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
42
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 21 publications
4
42
1
Order By: Relevance
“…Brain temperature never exceeded 40.5°C. However, the threshold for selective brain cooling in most artiodactyls is •39°C (see Fuller et al 1999a), and in horses it was reported to be •38°C (McConaghy et al 1995), near to the mode of blood temperature of zebras in our study. So if zebras have a threshold above 40.5°C, it would be the highest, by about 1.5°C, of all mammals studied so far.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…Brain temperature never exceeded 40.5°C. However, the threshold for selective brain cooling in most artiodactyls is •39°C (see Fuller et al 1999a), and in horses it was reported to be •38°C (McConaghy et al 1995), near to the mode of blood temperature of zebras in our study. So if zebras have a threshold above 40.5°C, it would be the highest, by about 1.5°C, of all mammals studied so far.…”
Section: Discussionsupporting
confidence: 51%
“…Our measurements on zebra add a fourth species, and the first perissodactyl, to our studies of ungulates, which previously included black wildebeest (Jessen et al 1994), springbok (Mitchell et al 1997) and eland (Fuller et al 1999a); these four studies remain the only continuous measurements of brain and arterial blood temperatures in free-ranging animals in their natural habitat. Our new study was the first to measure brain and blood temperatures in a free-ranging mammal that does not have a carotid rete, the anatomical structure usually associated with selective brain cooling.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations